Proteostasis by STUB1/HSP70 complex controls sensitivity to androgen receptor targeted therapy in advanced prostate cancer. Issue 1 (December 2018) - Liu, Chengfei; Lou, Wei; Yang, Joy; Liu, Liangren; Armstrong, Cameron; Lombard, Alan; Zhao, Ruining; Noel, Onika; Tepper, Clifford; Chen, Hong-Wu; Dall'Era, Marc; Evans, Christopher; et al.
Abstract Protein homeostasis (proteostasis) is a potential mechanism that contributes to cancer cell survival and drug resistance. Constitutively active androgen receptor (AR) variants confer anti-androgen resistance in advanced prostate cancer. However, the role of proteostasis involved in next generation anti-androgen resistance and the mechanisms of AR variant regulation are poorly defined. Here we show that the ubiquitin-proteasome-system (UPS) is suppressed in enzalutamide/abiraterone resistant prostate cancer. AR/AR-V7 proteostasis requires the interaction of E3 ubiquitin ligase STUB1 and HSP70 complex. STUB1 disassociates AR/AR-V7 from HSP70, leading to AR/AR-V7 ubiquitination and degradation. Inhibition of HSP70 significantly inhibits prostate tumor growth and improves enzalutamide/abiraterone treatments through AR/AR-V7 suppression. Clinically, HSP70 expression is upregulated and correlated with AR/AR-V7 levels in high Gleason score prostate tumors. Our results reveal a novel mechanism of anti-androgen resistance via UPS alteration which could be targeted through inhibition of HSP70 to reduce AR-V7 expression and overcome resistance to AR-targeted therapies. The AR-V7 isoform is associated with anti-androgen drug resistance in prostate cancer. Here, the authors show that AR-V7 protein stability is regulated by HSP70/STUB1 complex-mediated proteostasis which confers drug resistance in late stage prostate cancer. Inhibition of HSP70 re-sensitizes resistant cells to enzalutamide therapy.